2021
DOI: 10.7717/peerj.11441
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA panel in serum reveals novel diagnostic biomarkers for prostate cancer

Abstract: Purpose MicroRNAs (miRNAs), which could be stably preserved and detected in serum or plasma, could act as biomarkers in cancer diagnosis. Prostate cancer is the second cancer in males for incidence. This study aimed to establish a miRNA panel in peripheral serum which could act as a non-invasive biomarker helping diagnosing PC. Methods A total of 86 PC patients and 86 normal control serum samples were analyzed through a four-stage experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Table 1A represents the data from our EV literature search in PubMed, Embase, and Google Scholar. In our corpus of 31 articles, [ 9–13,17–42 ] miR‐21‐5p, miR‐141‐3p, and miR‐375‐3p were among the most represented (Table 1A). We cross‐referenced these data with Table 1B, which lists the dysregulated miRNA from our DESeq2 analysis (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Table 1A represents the data from our EV literature search in PubMed, Embase, and Google Scholar. In our corpus of 31 articles, [ 9–13,17–42 ] miR‐21‐5p, miR‐141‐3p, and miR‐375‐3p were among the most represented (Table 1A). We cross‐referenced these data with Table 1B, which lists the dysregulated miRNA from our DESeq2 analysis (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is considered essential to apply a panel of several miRNAs linked to a condition of interest so that a profile of expression changes is generated, rather than relying on a single miRNA [ 151 , 152 ]. Such panels have been developed previously for cardiovascular conditions such as myocardial infarction [ 153 ], dilated cardiomyopathy [ 151 ] and have been applied for prognostic and diagnostic purposes in other conditions including breast cancer [ 154 ], prostate cancer [ 155 ] and non-small cell lung cancer [ 156 ]. The nature of the chemotherapy agent appears to play a significant role in the expression of miRNAs as different agents elicited responses in different markers.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have evaluated the other mature sequence of miR-24, miR-24-3p, which has been suggested as a diagnostic biomarker for prostate cancer in serum [ 48 , 49 ]. The circRNA protein kinase C-iota has been suggested to influence tumor development, and a study found this molecule triggers growth and metastasis in prostate cancer by downregulation of miR-24-3p [ 50 ].…”
Section: Discussionmentioning
confidence: 99%